Review of remediation practices regarding cadmium-enriched farmland soil with particular reference to China. (1st October 2016) - Tang, X.; Li, Q.; Wu, M.; Lin, L.; Scholz, M.
Abstract: Cadmium-enrichment of farmland soil greatly threatens the sustainable use of soil resources and the safe cultivation of grain. This review paper briefly introduces the status of farmland soil as well as grain, which are both often polluted by cadmium (Cd) in China, and illustrates the major sources of Cd contaminants in farmland soil. In order to meet soil environmental quality standards and farmland environmental quality evaluation standards for edible agricultural products, Cd-enriched farmland soil is frequently remediated with the following prevailing techniques: dig and fill, electro-kinetic remediation, chemical elution, stabilisation and solidification, phytoremediation, field management and combined remediation. Most remediation techniques are still at the stage of small-scale trial experiments in China and few techniques are assessed in field trials. After comparing the technical and economical applicability among different Cd-enriched farmland soil remediation techniques, a novel ecological and hydraulic remediation technique has been proposed, which integrated the advantages of chemical elution, solidification and stabilisation, phytoremediation and field management. The ecological and hydraulic remediation concept is based on existing irrigation and drainage facilities, ecological ditches (ponds) and agronomic measures, which mainly detoxify the Cd-enriched soil during the interim period of crop cultivation, and guarantee the grain safety during its growth period. This technique may shift the challenge from soil to water treatment, and thus greatly enhances the remediation efficiency and shortens the remediation duration. Moreover, the proposed ecological and hydraulic remediation method matches well with the practical choice of cultivation while remediation for Cd-enriched soil in China, which has negligible impacts on the normal crop cultivation process, and thus shows great potential for large area applications. Graphical abstract: Concept of ecological and hydraulic remediation regarding farmland soil enriched by cadmium in China. Highlights: In China, cadmium is the most important metal in farmland soil contamination. Review: electro-kinetic; elution; solidification & stabilisation; phytoremediation. Soil remediation while cultivation is most practical for cadmium management. Integration: chemical elution; solidification & stabilisation; phytoremediation. Ecological and hydraulic remediation is promising in detoxifying soil cadmium.